Java programming with Berkeley DB XML explained through examples. - Mimaroglu, Selim
Berkeley DB XML (BDB XML) is a popular native XML database. It can be accessed through the shell or within another program. This month I will show you how to use BDB XML in Java. BDB XML has similar APIs for all supported languages such as Java and C++, therefore the ideas presented in this article apply to all supported langauges. I have been closely following BDB XML from the very first release, and there have been tremendous improvements in this product.